Comprehensive Study on Cr(VI) Adsorption and Regeneration Behavior of Alkali-Treated Wood Charcoal: Isotherms and Kinetics Models - Afandy, Moh. Azhar; Sawali, Fikrah Dian Indrawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The present study considers the adsorption and regeneration behavior of alkali-treated wood charcoal (WC-NaOH and WC-KOH) for Cr(VI) removal. Adsorption isotherms (Langmuir, Freundlich, Temkin, and Dubinin-Raduskevich) and kinetics (Pseudo-first-order and Pseudo-second-orderare being investigated utilizing a non-linear method that provides precise parameter prediction and mechanism elucidation. The outcomes suggested that both WC-NaOH and WC-KOH exhibit good Cr(VI) removal efficiency, with the Langmuir model best explaining the adsorption phase, indicating single-layer adsorption. The kinetic study revealed that the Pseudo-second-order model aligns remarkably well with the data, thereby affirming that chemical adsorption is the predominant mechanism in consideration. A comparative analysis revealed that WC-KOH exhibits a higher amount of adsorption than WC-NaOH, attributable to its enhanced larger surface area as well as micro-porous structure.. Regeneration studies showed the possibility of reuse of both adsorbents. It shows the efficiency of alkali-treated wood charcoal for Cr(VI) decontamination and the advantages of non-linear modeling in adsorption experiments